Manajemen Konflik Dan Penyelesaiannya Dalam Pandangan Islam - Ghufron, Ghufron (At-Turost : Journal of Islamic Studies, 2021)
The focus of the study in this article includes the nature of conflict and views of conflict in organizations, the process of conflict in organizations, forms of conflict in organizations, overcoming and managing conflict in organizations, the impact of conflict on performance, management of interpersonal conflict in Islamic views. The study in this article is to use a literature review of management and Islamic literature. After conducting an in-depth discussion, it can be concluded that conflict cannot be avoided, so a good approach for managers to apply is one that tries to exploit conflict in such a way that it can contribute effectively to achieving the desired goals. Conflict can actually be a strong energy if it is managed properly, so that it can be used as an innovation tool. However, if it cannot be controlled, it will result in low organizational performance. From a manager is required to optimize all conflicts into functional. Failure in conflict management puts organizational effectiveness at stake. Given that conflict is unavoidable, a good approach for managers to adopt is one that tries to exploit conflict in Islamic ways so that conflict can contribute effectively and productively to the dynamics and future of the organization.